(3GdMbjHI GdfLajIs - (3cGXe eMeO Ydj TcQs ((3GdeDdas)
(3ChdgG (B:s
(3HSe Gddg (B.. (3gPG gh GdLRA GdQGHY ef GdMbjHI GdfLajI hgh cGdCLRGA GdSGHbI ChOYJ ajg GdHMhK hGdcdeGJ hGdOQGSGJ GdJj dG jLeYgG ehVhY ehMO hdG efGSHI hGMOI (B...s
(3BNQgG (B:s
... (3fYe gcPG cGf Bd GdLRGFQj hgcPG cGf eLdSge hgcPG cGf GYdGege JYgOge Gddg JYGdi HQMeJg hQVhGfg hCScfge aSjM LfGJg (B. (3GfJgi GdLRA GdQGHYs
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
(3MGdI GdfSNI (B:s
Keywords: (3GdeYGQa GdYGeIs